2022
DOI: 10.1186/s12951-022-01319-7
|View full text |Cite
|
Sign up to set email alerts
|

A drug-free nanozyme for mitigating oxidative stress and inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) is an incurable disease of the gastrointestinal tract with a lack of effective therapeutic strategies. The proinflammatory microenvironment plays a significant role in both amplifying and sustaining inflammation during IBD progression. Herein, biocompatible drug-free ceria nanoparticles (CeNP-PEG) with regenerable scavenging activities against multiple reactive oxygen species (ROS) were developed. CeNP-PEG exerted therapeutic effect in dextran sulfate sodium (DSS)-induced colit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…Exposure to Al 2 O 3 NPs leads to the phosphorylation of STAT3 and inhibition of PTPN6, eventually leading to the increased expression of the apoptosis marker PDCD4 [56] . In line with these findings, Zeng F. et al reported that cerium oxide NPs (CENPPEG) may downregulate ROS and numerous pro-inflammatory cytokines by inhibiting NF-κB and the JAK2/STAT3 signalling pathways, thereby countering the pro-inflammatory microenvironment and inhibiting the pro-inflammatory actions of macrophages and the Th1/Th17 response [57] , which highlights their potential anti-inflammatory effect.…”
Section: Signalling Pathways For the Regulation Of Inflammationmentioning
confidence: 72%
“…Exposure to Al 2 O 3 NPs leads to the phosphorylation of STAT3 and inhibition of PTPN6, eventually leading to the increased expression of the apoptosis marker PDCD4 [56] . In line with these findings, Zeng F. et al reported that cerium oxide NPs (CENPPEG) may downregulate ROS and numerous pro-inflammatory cytokines by inhibiting NF-κB and the JAK2/STAT3 signalling pathways, thereby countering the pro-inflammatory microenvironment and inhibiting the pro-inflammatory actions of macrophages and the Th1/Th17 response [57] , which highlights their potential anti-inflammatory effect.…”
Section: Signalling Pathways For the Regulation Of Inflammationmentioning
confidence: 72%
“…145 Therefore, eradicating ROS may have great potential for ameliorating the pro-inflammatory microenvironment and promoting mucosal healing in IBD so as to treat UC or CD. 30 Nanozymes, as a kind of nanomaterial with multiple enzyme-like activities, are characterized by their ability to eliminate reactive oxygen species and relieve oxidative stress (Table 2).…”
Section: Nanozymes For Inflammatory Diseasesmentioning
confidence: 99%
“…and inhibiting their activation, to achieve further anti-inflammation effects. [27][28][29][30] Hence, utilizing nanozymes as a 'drug' for these inflammatory diseases is feasible and has great potential for clinical translation.…”
Section: •−mentioning
confidence: 99%
See 1 more Smart Citation
“…106 Polyethylene glycol (PEG) is a synthetic polymer that is widely used for the modification of drugs to improve their physicochemical properties and biocompatibility. Zeng et al 108 prepared PEG-modified CeO 2 nanozymes for the treatment of inflammatory bowel disease, and the modified nanozymes had better biocompatibility (Figure 2A). Nie et al 109 proposed a modified PEG modification strategy for nanozymes.…”
Section: Functionalization Modification Of Nanozymesmentioning
confidence: 99%